2024
DOI: 10.3390/cryst14020152
|View full text |Cite
|
Sign up to set email alerts
|

From the Fibonacci Icosagrid to E8 (Part I): The Fibonacci Icosagrid, an H3 Quasicrystal

Fang Fang,
Klee Irwin

Abstract: This paper introduces a new kind of quasicrystal by Fibonacci-spacing a multigrid of a certain symmetry, like H2, H3, T3, etc. Multigrids of a certain symmetry can be used to generate quasicrystals, but multigrid vertices are not a quasicrystal due to arbitrary closeness. By Fibonacci-spacing the grids, the structure transit into an aperiodic order becomes a quasicrystal itself. Unlike the quasicrystal generated by the dual-grid method, this kind of quasicrystal does not live in the dual space of the grid spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…For non-crystallographic point symmetries such as H 2 (pentagonal) and H 3 (icosahedral), the regular grids have intersection points that are arbitrarily close to each other, but the Fibonacci spacing resolves this to provide finite minimal spacing, and therefore a discrete Fourier spectrum. In Part I of this series, Fang and Irwin have studied an H 3 version [21,22], referred to as the Fibonacci icosagrid (FIG), and have shown that it is closely related to sections of the Elser-Sloane quasicrystal (ESQC), a 4D quasicrystal derived by direct cut-and-project from the E 8 root lattice [23].…”
Section: Introductionmentioning
confidence: 99%
“…For non-crystallographic point symmetries such as H 2 (pentagonal) and H 3 (icosahedral), the regular grids have intersection points that are arbitrarily close to each other, but the Fibonacci spacing resolves this to provide finite minimal spacing, and therefore a discrete Fourier spectrum. In Part I of this series, Fang and Irwin have studied an H 3 version [21,22], referred to as the Fibonacci icosagrid (FIG), and have shown that it is closely related to sections of the Elser-Sloane quasicrystal (ESQC), a 4D quasicrystal derived by direct cut-and-project from the E 8 root lattice [23].…”
Section: Introductionmentioning
confidence: 99%